The Influences of Good Corporate Governance and Company Age on Integrated Reporting Implementation - Maharanny Yulyan; Winwin Yadiati; Said Aryonindito (Universitas Padjadjaran, 2021)
This study aims to determine Good Corporate Governance's effect and the firm's age on integrated reporting implementation. The corporate governance structure refers to the board of commissioners, independent commissioners, the audit committee, and the meeting attendance, the study employed company size as a control variable. Several mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018 were selected through a purposive sampling technique as the population of this study. Based on predetermined criteria, the selected samples of this study were 44 of 132 data. A quantitative method with descriptive statistics was chosen as a research design, and it also gained secondary data from the annual report as a data source. The study results revealed that the board of commissioners, the independent board, and the company's age and size as control variables influence integrated reporting implementation. Otherwise, the audit committee and meeting attendance do not affect the implementation of integrated reporting. Lastly, the board of commissioners, the board of independent commissioners, the audit committee, meeting attendance, company age and size as control variables jointly influenced integrated reporting implementation